Security problems in international tourism - Gaydukevich, Leonid M. (Journal of the Belarusian State University. International Relations, 2018)
The article contains analyses of the main issues related to security in the international tourism, gives characteristics to the main types of threats not only to health and life of tourists, but also to business entities that organize tourist trips. Analysis of the economic losses from tourism in Egypt, Turkey, Saudi Arabia and other countries shows the complex impact of terrorist acts and threats on the economic, historical and cultural capacity of these countries and tourist regions as a whole. This article explores the dynamics of growth of the total number of terrorist attacks on tourist sites in the Middle East, the Asia-Pacific region, which are directly linked to the activities of terrorist organizations such as “Al-Qaeda”, “Islamic State”, “Dzhabhaten-Nusra” and others. The author analyzes the main legal documents in the field of security adopted by the United Nations, World Tourism Organization and other specialized international organizations, to ensure the safety of tourist travel, proposes to increase the effectiveness of the regional commissions of the UNWTO, international cooperation of countries in these fields.